Mathematical modeling of an optimum foot strike pattern: effect of footwear and surfaces - Tang, Yew Seng. (2008)
This study investigated the relative contributions of shoes and surfaces on the spring and damping constants of a mass-spring-damper system modeled to describe the heel-toe running foot strike. The effects of shoes and surface interventions on ground contact time, first impact peak force, time to first impact peak force, vertical loading rate and second impact peak force were determined.